Dismissal of RNA Polymerase II Underlies a Large Ligand-induced Enhancer Decommissioning Program - Tan, Yuliang (Mol Cell, 2018)
Nuclear receptors induce both transcriptional activation and repression programs responsible for development, homeostasis and disease. Here, we report a previously overlooked enhancer decommissioning strategy underlying a large estrogen receptor alpha (ERα)-dependent transcriptional repression program. The unexpected signature for this E(2-)induced program resides in indirect recruitment of ERα to a large cohort of pioneer factor basally-active FOXA1-bound enhancers that lack cognate ERα DNA binding elements. Surprisingly, these basally-active estrogen-repressed (BAER) enhancers are decommissioned by ERα-dependent recruitment of the histone demethylase, KDM2A, functioning independently of its demethylase activity. Rather, KDM2A tethers the E3 ubiquitin-protein ligase, NEDD4, to ubiquitylate/dismiss Pol II to abrogate eRNA transcription, with consequent target gene down-regulation. Thus, our data reveal that Pol II ubiquitylation/dismissal may serve as a potentially broad strategy utilized by indirectly bound nuclear receptors to abrogate large programs of pioneer factor-mediated, eRNA-producing enhancers.